2018
DOI: 10.1016/j.ajog.2017.10.252
|View full text |Cite
|
Sign up to set email alerts
|

316: Novel anti-MBG antibodies protect cytotrophoblast cells from a marinobufagenin-induced preeclampsia phenotype

Abstract: OBJECTIVE: Preeclampsia (PreE) is a hypertensive pregnancy disorder. Marinobufagenin (MBG) has been implicated as a causative factor in preE. We demonstrated that MBG inhibits the proliferation, migration, and invasion of cytotrophoblast (CTB) cells. We have identified a novel human monoclonal antibody with higher specificity than Digibind for MBG. We assessed the attenuation of MBG-induced CTBs dysfunction by three anti-MBG antibodies: 206-208, H1L2, and 3e9. STUDY DESIGN: A panel of anti-MBG antibodies with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A recent work also showed that incubation of explants of umbilical arteries obtained from the patients with PE with monoclonal antibodies against MBG led to a significant decrease in collagen-1 content [37]. Besides, incubation of healthy human umbilical arteries in the presence of low MBG concentrations for 24 hours led to decline in the Fli1 content and an increase in PKC-delta expression, while the level of pro-collagen-1 synthesis increased six-fold [95]. Another work has shown that the introduction of humanized monoclonal antibodies to MBG leads to phosphorylation of MAP kinase p38 in cytotrophoblast cells, indicating a possible therapeutic effect of these antibodies [96].…”
Section: Discussionmentioning
confidence: 91%
“…A recent work also showed that incubation of explants of umbilical arteries obtained from the patients with PE with monoclonal antibodies against MBG led to a significant decrease in collagen-1 content [37]. Besides, incubation of healthy human umbilical arteries in the presence of low MBG concentrations for 24 hours led to decline in the Fli1 content and an increase in PKC-delta expression, while the level of pro-collagen-1 synthesis increased six-fold [95]. Another work has shown that the introduction of humanized monoclonal antibodies to MBG leads to phosphorylation of MAP kinase p38 in cytotrophoblast cells, indicating a possible therapeutic effect of these antibodies [96].…”
Section: Discussionmentioning
confidence: 91%
“…The incubation of healthy human umbilical arteries in the presence of low MBG concentrations for 24 h led to a decline in the Fli1 content and an increase in the PKC-delta expression while the level of procollagen-1 synthesis increased six-fold [ 37 ]. Another work has shown that the introduction of humanized anti-MBG monoclonal antibodies leads to phosphorylation of MAP kinase p38 in cytotrophoblast cells, indicating a possible therapeutic effect of these antibodies [ 57 ]. Moreover, a recent study has demonstrated that the silencing of Fli1 in human umbilical arteries mimics preeclamptic phenotypes through activating PKCδ and the activation of procollagen and collagen-1 synthesis [ 57 , 58 ].…”
Section: Immunoneutralization Of Cardiotonic Steroidsmentioning
confidence: 99%
“…Another work has shown that the introduction of humanized anti-MBG monoclonal antibodies leads to phosphorylation of MAP kinase p38 in cytotrophoblast cells, indicating a possible therapeutic effect of these antibodies [ 57 ]. Moreover, a recent study has demonstrated that the silencing of Fli1 in human umbilical arteries mimics preeclamptic phenotypes through activating PKCδ and the activation of procollagen and collagen-1 synthesis [ 57 , 58 ]. The antagonism of endogenous CS can be one of the new and fundamentally different possibilities of pharmacological therapy and prevention of vascular fibrosis.…”
Section: Immunoneutralization Of Cardiotonic Steroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in comparative study of the efficacy of specific antibodies with antidigoxin (DigiFab) and monoclonal antibody against MBG (3E9), it was shown that monoclonal antibodies restore the activity of PE-inhibited NKA in erythrocytes better than DigiFab, which suggested the involvement of MBG in the pathogenesis of PE [46]. In a recent study, it was shown that the administration of humanized monoclonal antibodies (206-208, H1L2) against MBG attenuate MBG-induced downregulated PCNA and upregulated p38 phosphorylation in cytotrophoblast cells, indicating a possible therapeutic action in PE [47]. erefore, immunoneutralization of MBG is a logical step in the treatment of PE.…”
Section: Monoclonal Antibodymentioning
confidence: 99%